Anthropometric and somatotype characteristics of world class male roller skaters by discipline - Vila, H.; Abraldes, J. A.; Rodriguez, N.; Ferragut, C. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The aim of this study was twofold: 1) to describe the anthropometric profile and somatotype of the elite male roller skaters; and: 2) to assess if there are any differences in these items by roller skating discipline (figures, freestyle, pair and dance).